Does the Aspartic Acid to Asparagine Substitution at Position 76 in the Pancreas Duodenum Homeobox Gene (PDX1) Cause Late-Onset Type 2 Diabetes? - Elbein, Steven C.; Karim, Mohammad A. (Diabetes care, 2004)
Does the Aspartic Acid to Asparagine Substitution at Position 76 in the Pancreas Duodenum Homeobox Gene ( PDX1 ) Cause Late-Onset Type 2 Diabetes? Steven C. Elbein , MD 1 2 and Mohammad A. Karim , MD, PHD 2 1 Central Arkansas Veterans Healthcare System, Little Rock, Arkansas 2 University of Arkansas for Medical Sciences, Little Rock, Arkansas Address correspondence and reprint requests to Steven C. Elbein, MD, Professor of Medicine, University of Arkansas for Medical Sciences, Endocrinology 111J-1/LR, JLM VA Hospital, 4300 West 7th St., Little Rock, AR 72205. E-mail: elbeinstevencatuams.edu Abstract OBJECTIVE —Considerable data support an inherited defect in insulin secretion as one component of type 2 diabetes. Coding variants of the pancreas duodenum homeobox gene ( PDX1 ) were proposed to predispose late-onset type 2 diabetes and to decrease transactivation in vitro. We tested the hypothesis that the Asp76Asn (D76N) variant that was identified in several populations predisposed type 2 diabetes and reduced insulin secretion. RESEARCH DESIGN AND METHODS —We performed a case-control study in 191 control subjects and 190 individuals with type 2 diabetes, all of European descent, then characterized the D76N variant in 704 members of 68 families. We compared the phenotypic characteristics of those with and without the variant by diagnostic status and determined the insulin secretory response to intravenous glucose and tolbutamide among nondiabetic family members. RESULTS —D76N was not associated with type 2 diabetes, either in our population or when all reported studies in Caucasians were combined. D76N did not segregate with diabetes among the families examined. Among D76N carriers, nondiabetic individuals had a lower waist-to-hip ratio and a trend to lower BMI than their diabetic counterparts. Diabetic carriers of D76N were significantly leaner by BMI ( P = 0.012) and tended to be younger than diabetic individuals with the D/D genotype. However, insulin secretion in response to oral and intravenous glucose challenge and to intravenous tolbutamide was not reduced in D76N carriers. CONCLUSIONS —The D76N variant of PDX1 does not significantly alter insulin secretion or act as a high-risk susceptibility allele for late-onset type 2 diabetes as proposed previously, although we cannot exclude a minor role in increasing risk of diabetes. AIRg, acute insulin response to glucose FSIGT, frequently sampled intravenous glucose tolerance test IGT, impaired glucose tolerance Footnotes A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. Accepted April 19, 2004. Received December 1, 2003. DIABETES CARE